Wettability modification to further enhance the pool boiling performance of the micro nano bi-porous copper surface structure. (April 2018) - Wang, Ya-Qiao; Luo, Jia-Li; Heng, Yi; Mo, Dong-Chuan; Lyu, Shu-Shen
Highlights: Combine both optimal cavity size and wettability modification to enhance pool boiling. Enlarging the size of dendrites on the pore wall is the priority wettability modification. The modified sample has lower interface energy making it easier for bubbles to depart. The heat transfer coefficient can be as high as 30 W cm −2 K −1 . Abstract: Boiling heat transfer is widely used in industry and in daily life and it can be enhanced by micro/nano surface modification. Herein, we study the pool boiling characteristics of the micro nano bi-porous copper surface with optimal cavity size from other researchers and present an efficient way to further enhance its boiling heat transfer performance by wettability modification of enlarging the particle size to lower the surface energy. In this work, two micro nano bi-porous copper surface samples were prepared and compared with conventional surfaces. One is the original micro nano bi-porous copper surface (Sample#O) prepared using the hydrogen bubble template deposition method to form abundant pores in optimal cavity size, and the other one is the modified micro nano bi-porous copper surface (Sample#M) that is modified by applying a low current density on Sample#O for a few minutes. Scanning Electron Microscope (SEM) images show that Sample#M keeps the pore size but enlarges the nano dendrite on the top of pore wall to micro balls. The conducted pool boiling experiments indicate that both micro nano bi-porous copper surfaces have superior heat transfer coefficients than the plain copper surface, and the high-speed camera shows that the micro nano bi-porous copper surfaces have shorter bubble growth periods than those surfaces with pure nano structure or pure micro structure. At a heat flux of 90 W cm −2, the heat transfer coefficient of Sample#O is 13 W cm −2 K −1, which is 2.8 times over that of the plain surface. Compared to Sample#O, Sample#M can further enhance the pool boiling heat transfer. At the same heat flux of about 90 W cm −2, the heat transfer coefficient of Sample#M is 23 W cm −2 K −1, which is 1.7 times over that of Sample#O and 4.8 times over that of the plain surface. The heat transfer coefficient of Sample#M can be as high as 30 W cm −2 K −1 when it reaches the CHF. High-speed camera images show that highest bubble growth period for Sample#M is just less than 20 ms, which is shorter than that of Sample#O having a value in between 20 ms and 40 ms. It confirms that Sample#M after wettability modification has a lower interface energy which can accelerate the bubbles departure, and has an even more superior heat transfer performance than Sample#O.